Complete sequences of the mitochondrial DNA of the Grateloupia filicina (Rhodophyta). Issue 1 (2nd January 2018) - Li, Yue; Meinita, Maria Dyah Nur; Liu, Tao; Chi, Shan; Yin, Hongxin
Abstract: In this study, we sequenced and analyzed the complete mitogenome of Grateloupia filicina (Lamouroux) C. Agardh. The complete G. filicina mitogenome was 29, 274-bp long, containing 51 genes, including 24 protein-coding genes, 1 intron, 2 rRNA genes, 24 tRNA genes, and 1 unidentified open reading frame. Twenty-one of the 24 (87.5%) protein-coding genes ended with the stop codon TAA, whereas 3 (12.5%) ended with TAG. All the protein-coding genes in G. filicina used the start codon ATG. Phylogenetic analysis revealed that G. filicina clustered with G. taiwanensis. The complete mitochondrial genome sequence provided here would be useful for understanding the evolution of Grateloupia further.